THE KHIBINY-LOVOZERO BINUCLEUS VORTEX STRUCTURE - Kulakovsky A.L. (My University, 2004)
It is concluded that structural position of Khibiny and Lovozero massifs was predetermined already in Precambrian Period, with formation of binucleus vortex structure upon shear deformation. Paleozoic activation of this structure (in arcogenic rifting mode?) is responsible for formation in the place of nuclei of the conical spallation zones, which controlled the alkaline massif development.